2021
DOI: 10.3389/fphys.2020.622179
|View full text |Cite
|
Sign up to set email alerts
|

Serum Renin Levels Increase With Age in Boys Resulting in Higher Renin Levels in Young Men Compared to Young Women, and Soluble Angiotensin-Converting Enzyme 2 Correlates With Renin and Body Mass Index

Abstract: Background: Age, sex, and body constitution may affect the shedding of membrane bound angiotensin-converting enzyme 2 (mACE2) and lead to a relative mACE2 deficiency. However, it is unclear if differences, reflected by serum renin levels, exist in the basal renin-angiotensin-system (RAS) between children and adults, boys, and girls as well as young women and young men. Furthermore, it remains to be investigated if renin and soluble ACE2 (sACE2) levels are correlated with body mass index (BMI) in children and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…For example, based on the distributions of angiotensins we observed in this study, we calculated that we would have 80% power to detect differences in circulating ANG II and ANG-(1–7) between COVID-19-negative and COVID-19-positive hospitalized patients with ∼127 participants per group. In similar regard, we were underpowered to explore the relationship between other potential confounding covariates that may alter the RAS in patients with COVID-19, such as age, sex, body mass index (BMI), and corticosteroid use ( 19 21 ). For instance, dexamethasone, which is now a standard of care in severe COVID-19 has been shown to upregulate ACE and ACE2 ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on the distributions of angiotensins we observed in this study, we calculated that we would have 80% power to detect differences in circulating ANG II and ANG-(1–7) between COVID-19-negative and COVID-19-positive hospitalized patients with ∼127 participants per group. In similar regard, we were underpowered to explore the relationship between other potential confounding covariates that may alter the RAS in patients with COVID-19, such as age, sex, body mass index (BMI), and corticosteroid use ( 19 21 ). For instance, dexamethasone, which is now a standard of care in severe COVID-19 has been shown to upregulate ACE and ACE2 ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older age, male gender and higher BMI may enhance mACE2 shedding, leading to relative mACE2 deficiency. Jehpsson et al (116) reported that renin levels increase with age and from puberty, these levels are elevated among men than in women with a positive correlation with sACE2 levels. In circulation, renin levels and activities are correlated with AngII levels (117).…”
Section: Gendermentioning
confidence: 97%
“…The tissue levels of mACE2 represent equilibrium between transcription/translation of mACE2 and shedding rate of sACE2. It was reported that a positive relationship exists between renin and sACE2 levels in male and female subjects, and between sACE2 levels and body mass index (BMI) in males, with possible implication for COVID-19 ( Jehpsson et al, 2021 ). Variations in mACE2 with age were first demonstrated using animal models ( Xie et al, 2006 ).…”
Section: The Human Ace2 Gene Variant Mrnasmentioning
confidence: 99%